Management of occult neck disease in metastatic squamous cell carcinoma to the parotid gland - Pollaers, Katherine; Davidoss, Nishant; Hinton-Bayre, Anton (Australian Journal of Otolaryngology; Vol 2 (October 2019): Australian Journal of Otolaryngology, 2019)
Background: Metastatic cutaneous squamous cell carcinoma (cSCC) to the parotid gland is associated with poor prognostic outcomes. The presence of metastatic cSCC to the parotid represents at least stage III disease, and is typically treated with bimodal therapy in the form of surgery and post-operative radiation therapy. At present, there is no consensus on the optimal management of potential occult neck metastases in the parotid positive and clinically and radiologically neck negative patient. We sought to evaluate whether elective neck dissection conferred a survival benefit in this cohort, when performed in conjunction with parotidectomy. Methods: Theatre management software was interrogated to identify all patients who underwent “parotidectomy” during the study period. Histopathology reports were then reviewed to identify patients with metastatic cSCC. Chart review was undertaken to determine suitability for inclusion. Clinical charts were reviewed and coded for demographics, clinical presentation, radiologic findings, surgical notes, inpatient stay, post-operative radiation treatment, and outpatient consultations. The Western Australian Cancer Registry was interrogated for recurrence and mortality data and cross-referenced with chart review information to provide the primary end-points of disease-free and overall survival. Results: Ninety-five patients met inclusion criteria. Sixty-two of the 95 patients with metastatic cSCC to the parotid without clinical/radiological neck disease underwent elective neck dissection. Patients who underwent neck dissection were more likely to present with an active primary (21% vs. 3%), and had more advanced parotid pathology (stage 2 or more, 60% vs. 33%), as classified by the O’Brien P stage. The rate of occult neck metastases in the neck dissection group was 25.8%, mainly seen in level 2 when dissected. The 5-year disease-free survival for the cohort was 33.5%, the overall 5-year survival was 42.5%. Elective neck dissection did not confer a 5-year disease-free or overall survival benefit. Conclusions: The prognosis of metastatic cSCC to the parotid is poor. No method has been established to predict those who will have occult neck metastases, with an observed range of 15–44% across studies. Elective neck dissection remains an option for the P+N0 parotid SCC case, and may be of benefit in select cases, including those with active primary disease or more advanced parotid pathology. The extent of neck dissection to be performed also remains unclear, but levels 2 and 3 are likely beneficial. Larger controlled studies of this group are warranted given the poor survival outcomes.